Acute Management of Renal Colic and Compliance with National Standards: Closure of the Audit Loop - Goonewardene SS P Rajjayabun (Archives of Renal Diseases and Management - Peertechz Publications, 2016)
Renal (ureteric) colic is a common surgical emergency. It is usually caused  by  calculi  obstructing  the  ureter,  but  about  15%  of  patients have  other  causes,  e.g.  extrinsic  compression,  intramural  neoplasia or an anatomical abnormality [1]. Up to 12 percent of the population will  have  a  urinary  stone  during  their  lifetime,  and  recurrence  rates approach  50  percent  [2].  Fifty-five  percent  of  those  with  recurrent stones have a family history of urolithiasis [3] and having such a history increases the risk of stones by a factor of three [4]. Upon presentation to the A&E department, suspected acute renal colic patients must have a  clinical  examination  and  radiological  investigations  to  confirm  the diagnosis [5]. The  best  imaging  study  to  confirm  the  diagnosis  of  a  urinary stone  in  a  patient  with  acute  flank  pain  is  unenhanced,  helical  CT  of the  abdomen  and  pelvis  [6].  If  CT  is  unavailable,  plain  abdominal radiography  should  be  performed,  since  75  to  90  percent  of  urinary calculi are radiopaque [5]. Although ultrasonography has high specificity (greater than90 percent), its sensitivity is much lower than that of CT, typically in the range of 11 to24 percent [5]. Thus, ultrasonography is not  used  routinely  but  is  appropriate  as  the  initial  imaging  test  when colic occurs during pregnancy [7].